2008
DOI: 10.1148/radiol.2492080033
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Multidetector CT in Patients with Varying Body Fat Percentages: Estimation of Optimal Contrast Material Dose

Abstract: Excessive contrast material may inadvertently be given in heavier patients when the dose is determined by patient BW. Contrast material dose may need to be tailored in individual patients by using BFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 20 publications
4
48
1
1
Order By: Relevance
“…Therefore, obese patients have a tendency to receive unnecessarily high doses of contrast media while muscular patients may receive doses that are too low. The observation of an association between abdominal fat and hepatic enhancement in the present study is consistent with some previous observations (11,13). Ho et al (11) reported that body fat proportion affected hepatic enhancement greatly, and that calculations of contrast media dose on the basis of measured lean BW marginally increased patient-to-patient uniformity with respect to hepatic parenchyma and vascular enhancement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, obese patients have a tendency to receive unnecessarily high doses of contrast media while muscular patients may receive doses that are too low. The observation of an association between abdominal fat and hepatic enhancement in the present study is consistent with some previous observations (11,13). Ho et al (11) reported that body fat proportion affected hepatic enhancement greatly, and that calculations of contrast media dose on the basis of measured lean BW marginally increased patient-to-patient uniformity with respect to hepatic parenchyma and vascular enhancement.…”
Section: Discussionsupporting
confidence: 93%
“…Although anthropometric markers such as waist circumstance and body mass index are conveniently measured, they are estimates and are not accurate. Kondo et al (13) used body fat percentage to evaluate the association between body fat and hepatic enhancement, and their results indicated that the correlation with hepatic enhancement was higher for body fat percentage than for other anthropometric markers. However, the measurement of body fat percentage requires a special instrument that is not always available.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also indicated a weakly positive association between the patient's body weight and contrast enhancement of the liver and portal vein during the hepatic venous phase for both contrast media and both injection schemes. This trend is in agreement with the results of a recent study [28] and supports the concept that a body weight-tailored approach for determining contrast medium dose may result in inconsistent enhancement among different patients. Such an approach could lead to (1) excessively high doses of contrast material in heavier patients, thus increasing the risk of renal toxicity and material cost, or (2) inappropriately low doses in smaller patients, thus compromising the diagnostic quality of the CT examination.…”
Section: Effect Of Contrast Materials Iodine Concentrations During LIVsupporting
confidence: 91%
“…Such an approach could lead to (1) excessively high doses of contrast material in heavier patients, thus increasing the risk of renal toxicity and material cost, or (2) inappropriately low doses in smaller patients, thus compromising the diagnostic quality of the CT examination. Other more accurate descriptors of a patient's body composition, such as lean body weight, body surface area and blood volume, appear promising and are currently under investigation for reducing interpatient variability of contrast medium enhancement on abdominal MDCT [28][29][30].…”
Section: Effect Of Contrast Materials Iodine Concentrations During LIVmentioning
confidence: 99%
“…Although using a fixed dose of contrast medium has been shown to be easy to implement and is generally effective, it can result in an under-or over-dosage of contrast medium in many patients [1] [2]. Preliminary evidence suggests that determining the dose and injection rate of contrast material administration based on the patient's lean body weight (LBW) may improve patient-to-patient enhancement variability during vascular and abdominal MDCT [2]- [5].…”
Section: Introductionmentioning
confidence: 99%